2022
DOI: 10.1590/1980-5373-mr-2021-0318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Control Agents on Fe-15at.%Nb powder during Mechanical Alloying

Abstract: In this paper, Fe-15at.%Nb alloys were produced from high purity Fe (min. 99.8%) and Nb (min. 99.8%) powders via a mechanical alloying process. The effects of different Process Control Agents (i.e., methanol, hexane, and stearic acid) were investigated with powder morphologies, particle size distribution, and phase formation, and were sampled after up to 80 milling hours at 350 rpm. The powder morphologies and particle sizes were evaluated using scanning electron microscopy and laser diffraction analysis, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Milling often facilitates the appearance of Fe-B compounds in alloys with Fe and B; however, in Nb-B milling, the Nb(B)-rich phase identified in this study was also reported in the literature [12][13][14][15][16][17][18]. The reaction between B and Nb is attributed to the negative mixing enthalpy which is about −39 kJ/mol.…”
Section: Xrd Analysissupporting
confidence: 66%
See 1 more Smart Citation
“…Milling often facilitates the appearance of Fe-B compounds in alloys with Fe and B; however, in Nb-B milling, the Nb(B)-rich phase identified in this study was also reported in the literature [12][13][14][15][16][17][18]. The reaction between B and Nb is attributed to the negative mixing enthalpy which is about −39 kJ/mol.…”
Section: Xrd Analysissupporting
confidence: 66%
“…It is evident the preparation conditions affect the final product and the mechanically alloyed powders' properties. The mechanical alloying technique is characterized by the repeated welding and fracturing of powder particles in a high-energy ball mill, which frequently results in excessive cold welding and ductile particle aggregation [14]. Even though agglomeration is a significant issue in the preparation process when the particulate size is reduced to the micron level, Hong and Kao [15] successfully incorporated very fine SiC particulates with a mean particle size of 0.3 mm into an Al matrix using the mechanical alloying (MA) process, which was used to improve the agglomeration of the reinforcement particulates as well as to reduce their crystalline size.…”
Section: Introductionmentioning
confidence: 99%